Islamic treatment/approach to drug addiction treatment in Malaysia - Jazaeri, S.A.; Habil, H.; Rashid, R.; Siddiq, A.; Zahari, M.M.; Peters, H. (2010)
This essay discusses the importance of assessing the religious condition of persons in drug addicted people and their counseling. Undertaking such assessments via the use of explicit theological terms assures a unique role for psychologists and psychiatrist in the helping process and provides a model that avoids overdependence on psychotherapy/psychology or psychiatry. For this reason, drug rehab centers in Malaysia such as UMCAS (University of Malaya Center of Addiction Science) or Khafidz Group Centers in Malaysia have dotted the national providing drug rehab treatment for the extremely pious or for those who are searching to find religion on their path to recovery from drug addiction. The activity of religious organizations raises many disputes primarily because they have emerged relatively recently as actors of antidrug policy and there is practically no unified opinion concerning their âusefulnessâ or âharmfulnessâ in combating drug abuse in Malaysia. Utilizing a method named: Islamic relaxation, proposed by Mardiyono, the development of a psychometrically sound interview and inventory is described. These methods/Islamic beliefs have been found to relate positively to mental health and personality strength among people who are recovering from drug addiction. The importance of using such Islamic/religious assessments of functional theology in helping persons grow in spiritual living and effective functioning is described. Suggestions for improving the psychology-religion interface are given.